Permainan Anak Usia Dini dalam Perspektif Islam - Khadijah Khadijah; Lasma Roha Sitompul (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2020)
This study aims to explain the position of children's play in an Islamic perspective. This study uses non-interactive qualitative methods, namely research on concepts through a document analysis. In conducting non-interactive qualitative research, the researcher identifies, studies, then synthesizes the available data to provide an understanding of the concept under study. The results of this study indicate that early childhood games are a tool used by children in playing activities so that these activities become very interesting and memorable for them. In the Early Childhood games there are those that are allowed and some which are prohibited by religion. Basically all games are allowed as long as they do not contain any harm in them. Early childhood games which are mandated by Islam are swimming, archery, spinning or making works by hand. Games that are prohibited in Islam such as gambling, chess, online games where the harm that is received is more than the benefits. Early Childhood is a time full of the world of games, where play is their life. Much of their daily life is spent playing, even the bed is also used as an object for playing. As if their motto is no day without playing.